Autonomic Neuropathy In Acute Ciclosporin Toxicity - Afzal, Hania; Naseer, Muhammad Asif; Jamshed, Abeerah; Ain, Qurat Ul (Journal of Rawalpindi Medical College, 2026)
Cyclosporine is associated with several well-known adverse effects; however, autonomic insufficiency related to the drug is rarely described in the literature. We report the case of a 72-year-old male pediatrician from Karachi, Pakistan, who was receiving cyclosporine for pure red-cell aplasia. He presented with dizziness, recurrent falls, tremulousness, and urinary incontinence. Examination revealed a significant postural drop in systolic blood pressure and fine resting tremors. Although specific autonomic testing was unavailable, the clinical picture and supporting investigations strongly suggested the presence of autonomic dysfunction. His cyclosporine level was markedly elevated (947.1 ng/mL). Discontinuation of cyclosporine, along with supportive management, led to rapid improvement in blood pressure, tremors, and urinary symptoms. The medication was later restarted at a lower dose with close therapeutic drug monitoring. This case highlights a rare presentation of autonomic neuropathy secondary to acute cyclosporine toxicity and underscores the need for vigilant monitoring, prompt recognition, and further research into this uncommon complication. Keywords: Cyclosporine; Drug Toxicity; Autonomic Nervous System Diseases; Orthostatic Hypotension; Tremor; Urinary Incontinence; Pure Red-Cell Aplasia